2019
DOI: 10.1002/ldr.3417
|View full text |Cite
|
Sign up to set email alerts
|

Converting forests into rubber plantations weakened the soil CH4 sink in tropical uplands

Abstract: Large‐scale conversion of natural forest to rubber plantations has taken place for decades in Southeast Asia, help to make it a deforestation hot spot. Besides negative changes in biodiversity, ecosystem water, and carbon budgets, converting forests to plantations often reduced CH4 uptake by soils. The latter process, which might be partly responsible for resumed increase in the growth rate of CH4 atmospheric concentrations since 2006, has not been adequately investigated. We measured soil surface CH4 fluxes d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 58 publications
(90 reference statements)
1
9
0
Order By: Relevance
“…Our results indicated that land use change from primary forest decreased soil CH 4 oxidation through modifying soil properties. Insufficient air constrained methanotroph activity due to the increase in soil bulk density and soil water filled pore space (Fest, Wardlaw, Livesley, Duff, & Arndt, ; Gutlein, Gerschlauer, Kikoti, & Kiese, ; Lang et al, ). Although there was negative effect of primary forest conversion on soil water holding capacity, illustrated by decreased soil moisture and organic matter, its positive impact on CH 4 oxidation might be overridden by other moderators that constrain CH 4 uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that land use change from primary forest decreased soil CH 4 oxidation through modifying soil properties. Insufficient air constrained methanotroph activity due to the increase in soil bulk density and soil water filled pore space (Fest, Wardlaw, Livesley, Duff, & Arndt, ; Gutlein, Gerschlauer, Kikoti, & Kiese, ; Lang et al, ). Although there was negative effect of primary forest conversion on soil water holding capacity, illustrated by decreased soil moisture and organic matter, its positive impact on CH 4 oxidation might be overridden by other moderators that constrain CH 4 uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Ray et al [19] found more areas would be suitable for rubber tree plantation in the NE region, whereas further expansion would be limited in the WG region under the projected climate scenario for 2050. Using a statistical regression model (SRM), Lang et al [20] disentangled the links between soil water content, soil texture, and mineral nitrogen in rubber plantations and assessed the impacts of land-use change on methane flux. Land surface models are also increasingly adopted to investigate the impact of land-use change on carbon and energy fluxes at various temporal and spatial scales [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the capacity of soil CH 4 uptake increased with the time since land use change under land restoration (Figures 3 and 6f). These results suggested that the capacity of CH 4 oxidation could lose rapidly and recover slowly in response to land degradation and restoration, respectively (Bárcena et al, 2014;Lang et al, 2019;Levine et al, 2011;Petitjean et al, 2019). Land degradation, such as the natural forest converted to plantation or cropland, is always associated with the clear-cutting, fertilization, and other intensive disturbances.…”
Section: Differential Response Of Soil Ch 4 Uptake To Land Degradatmentioning
confidence: 99%
“…Surprisingly, the effect of land degradation on soil CH 4 uptake rate seems to be independent of the time since land use change. For instance, the conversion of natural forest to other land use types can significantly decrease soil CH 4 uptake rate in a very short time interval (less than 10 years; Lang et al., 2019; Petitjean et al., 2019). However, it is unclear whether this phenomenon is common in various terrestrial ecosystems worldwide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation